Using a Herd Profile to Determine Age-Specific Prevalence of Bovine Leukemia Virus in Michigan Dairy Herds - Ronald J. Erskine; Paul C. Bartlett; Todd M. Byrem; Chelsea L. Render; Catherine Febvay; Jessica T. Houseman (Veterinary Medicine International)
Enzootic bovine leukosis is a contagious disease of cattle caused by the retrovirus, bovine leukemia virus (BLV) and is the most common cause of malignant neoplasm in cattle. In order to facilitate surveillance of this disease in dairy herds, we developed a method to combine ELISA of milk collected during routine production testing with a prescribed sampling of cows that is independent of the proportion of cows within each lactation. In 113 Michigan dairy herds, milk samples from ten cows in each of the 1st, 2nd, 3rd, and ≥4th lactations were analyzed for anti-Bovine Leukemia Virus (BLV) antibodies by milk ELISA. For each herd, a BLV herd profile (BHP) was calculated as the simple average of the percent of BLV-positive cows within each of the four lactation groups. The mean BHP for all herds was 32.8%, with means of 18.5, 28.8, 39.2, and 44.8% of 1st, 2nd, 3rd, and ≥4th lactation animals infected, respectively. In eight herds, we determined the correlation between the BHP, and true herd prevalence by testing the entire lactating herd (r=0.988,  P<0.0001). The BHP allows discrimination of lactation-specific BLV prevalence within a dairy herd, to help identify risk factors and management plans that may be important in transmission of BLV.